Analisis Kelebihan dan Kekurangan Teknik Equivalence Partitioning dan Boundary Value Analysis dalam Pengujian Perangkat Lunak - Silvi Hindun Mayrohmah; Awal Adi Saputro; Iqbal Ahmad Bukhari; Muhammad Nurfauzi Sahono (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The increasing complexity of web-based information systems has raised the demand for high-quality software, making the testing process an indispensable stage in the software development life cycle. One of the most widely used functional testing methods is Black Box Testing; however, its effectiveness is highly influenced by the test case design techniques employed. This study aims to analyze the implementation of Equivalence Partitioning (EP) and Boundary Value Analysis (BVA) within the Black Box Testing method through a literature review approach. The research employed a literature review method with a descriptive qualitative approach using secondary data collected from 15 national and international scientific articles published between 2022 and 2026. The analysis was conducted through the processes of identification, classification, comparison, and synthesis of previous studies discussing the implementation of EP, BVA, and their combination in various web-based information systems. The synthesis results indicate that the Equivalence Partitioning technique is more effective in improving testing efficiency by reducing the number of test cases, whereas Boundary Value Analysis is more effective in detecting validation errors at boundary values. Furthermore, the reviewed studies consistently demonstrate that combining both techniques provides more comprehensive test coverage than using either technique independently, as it achieves a balance between efficiency and effectiveness in the software testing process.